Peningkatan Kapasitas Desa Ngandong Dalam Upaya Mewujudkan Desa Tangguh Bencana - Akbar Bayu Pamungkas; Almahdi Dwita Purnama; Bebi Sylvia Muryanto; Diantara Nur Alam; Mutiara Kharisawati; Nur Arikhan Najmudin; Rachel Saniscara Nugraheni; Rachma Meika Maryanti; Rani Hapsari (Lembaga Pengembangan Kinerja Dosen, 2024)
Ngandong Village, Gantiwarno District is the village designated to be the location for implementing KKN with the theme Disaster Resilient Village. The problems faced by Ngandong Village based on the results of research conducted include sedimentation, landslides and flooding. The aim of holding KKN in Ngandong Village is to ensure that Ngandong Village can become a Disaster Resilient Village and increase the capacity of the village community in the context of disaster management. Activities carried out in efforts to develop Disaster Resilient Villages include FPRB (Disaster Risk Reduction Forum), SPAB (Disaster Safe Education Unit), Volunteer Capacity Building, Disaster Literacy, Evacuation and Disaster Prone Route Signs, Disaster Recap and Socialization Maps, and making EWS Tools (Early Warning System). Apart from the main activities, there are supporting activities to increase capacity in the form of Ecoprint training and decorating Pertiwi Kindergarten.